Evaluation of school literation movements in improving student discipline - Desy Natalia Sinambela; Syarwani Ahmad (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The goal of this study is to assess SMP Negeri 7 Palembang's School Literacy Movement in Improving Student Discipline. With the CIPP model, this analysis uses a qualitative approach that includes: 1. 1. Evaluating Meaning, 2. Evaluating Input, 3. Evaluation of Operation, and 4. Service Evaluation. The data analysis techniques used in this study are data reduction, presentation of data, conclusion and verification. The analyzed data is the product of SMP Negeri 7 Palembang citizens' interviews, observations, and documentation. This research shows that the School Literacy Movement's assessment of enhancing student discipline, The school has provided such facilities and resources in support of literacy programs, which include reading cornersBy providing 15 minutes to read before carrying out learning activities at the reading habit level,  And with some students, the School Literacy Movement has a positive effect on the work of literacy programs carried out by student achievement, It can be done and in SMP Negeri 7 Palembang there is a growth of character as well as a decision that this School Literacy Movement must be strengthened.